Identification of an endophytic Nodulisporium sp from Quercus ilex in central Spain as the anamorph of Biscogniauxia mediterranea by rDNA sequence analysis and effect of different ecological factors on distribution of the fungus (MYCOLOGIA, 2001)
A study of fungal endophytes from aerial parts of Quercus ilex ssp. ballota was carried out on 32 specimens sampled at three forests in Central Spain. Trunk bark, fresh leaves, and healthy and decaying twigs were surveyed. A Nodulisporium sp. was frequently recorded among the isolates. Sequence analysis of the internal transcribed spacer (ITS) region of the rDNA (including the 5.8S rRNA gene) was used for the identification of this fungus. The comparison and phylogenetic analysis of the sequences from several representatives of this endophytic species and a group of xylariaceous fungi with Nodulisporium-like anamorphs revealed that the endophytic Nodulisporium sp. was conspecific with the phytopathogenic species Biscogniauxia mediterranea (equivalent to Hypoxylon mediterraneum). Significant differences were found between the isolation frequencies of the fungus, relative to the geographical origin of the samples. Also, the fungus was more frequent on samples collected in the autumn, as compared to those collected in the spring. The greatest degree of colonization was observed in twigs, while in leaves the fungus was present in significantly lower amounts. The relative frequency of this species in bark increased in the higher parts of the trunk. Tissue preference analysis revealed that this fungal species is exclusively located in bark, being absent from xylem of living twigs. The relative abundance of the fungus in decaying twigs was remarkably higher than in healthy twigs.

Host specificity in fungal endophytic populations of Quercus ilex and Quercus faginea from Central Spain (NOVA HEDWIGIA, 2000)
A comparative study of the endophytic fungal assemblages of Quercus ilex subsp. ballota and Quercus faginea subsp. faginea was carried out on 10 trees growing in a Mediterranean forest in Central Spain. Endophytes from bark, twigs and fresh leaves were isolated from both tree species. As observed for other taxonomically related hosts, a certain overlapping between the endophytic mycoflora in both Quercus species was found. The most frequent fungus in both host species was Pyrenochaeta sp., an anamorph of Dothideales. Nevertheless, a certain degree of host specificity in fungal endophytic infection was detected, when the frequencies of the most commonly isolated endophytes were statistically analysed. The tree species affects significantly the distribution of almost all the fungi with isolation frequencies equal or higher than 2%. Moreover, some dominant fungal taxa could be isolated only from a particular host (Q. ilex or Q. faginea). A cluster analysis of the trees computed on the base of the similarity of their whole of fungal populations confirmed that there is an evident influence of the host species on the composition of the fungal assemblages of the trees. However, this effect does not appear to be always the main determinant of the composition of the fungal assemblages analysed.

Geographical and seasonal influences on the distribution of fungal endophytes in Quercus ilex (New Phytologist, 1999)
A systematic survey of the endophytic assemblages of Quercus ilex in central Spain has been performed, with the goal of evaluating the importance of geographical and seasonal factors on these fungal communities. Four sampling sites were selected; one of them was sampled twice, in the spring and the autumn. The collected plant material consisted of bark, twigs and leaves from eight trees per site. Fungal strains were isolated with the use of a surface-sterilization method with sodium hypochlorite. A total of 2921 fungal strains grouped into 149 ‘species’ or morphological types were recovered. The 10 dominant species, with isolation frequencies >1.5%, were Pyrenochaeta sp., Periconiella anamorph of Biscogniauxia mediterranea (De Not.) Kuntze, Pseudonectria sp., Cryptosporiopsis quercina Petrak, Alternaria alternata (Fr:) Keissl., two undetermined coelomycetes, Penicillium funiculosum Thom, Diplodia mutila Fr. apud Mont. and Ascochyta sp. Medians of fungal species per tree were significantly different among the sampled sites. The isolation frequencies of the dominant species, as well as other less frequent species, were significantly dependent on the sampling site. The degree of endophytic infection and the diversity of fungal species were significantly higher in the spring. The frequencies of all dominant species at one of the sites depended significantly on the season, except for C. quercina, Acremonium sclerotigenum (F & V Moreau ex Valenta) Gams. and D. mutila. Cluster analysis of the whole endophytic mycoflora of the sampled trees suggested that the geographical factor affects the endophytic distribution patterns more significantly than the seasonal factor.

Fungal endophytes in leaves, twigs and bark of Quercus ilex from Central Spain (NOVA HEDWIGIA, 1996)
Fungal endophytes were isolated from leaves, twigs and bark discs of the main stem of 16 individuals of Quercus ilex at two sites in the forests of El Pardo, Madrid, central Spain. From 512 segments of each sample type, 1084 fungal isolates were obtained, distributed among 98 species of filamentous fungi, yielding about 21 species/tree. Four isolation media were tested, which showed different behaviour depending on the type of sample. The use of fungitoxic compounds, such as benomyl or cycloheximide, resulted in a decrease in the number of isolates and species recovered, especially from leaves. Most of the dominant fungal species were not isolated from the four media indistinctly, but were preferentially recovered from one of the media. Twigs exhibited a higher degree of fungal infection than bark discs and leaves. The mycota isolated from bark and twigs were more similar to each other than to the fungal populations recovered from leaves. The frequency of isolation of most of the dominant fungal species depended significantly upon the sample type. A Phoma sp. was the only taxon similarly distributed among the three sample types. The height from which the bark discs were removed also influenced the population recovered. Both sampling sites were similar with respect to the number of species recovered from twigs and bark discs, but differed in the number of species from leaves. As in other plant and non-plant fungal communities, the population recovered from Q. ilex was characterized by a few species which accounted for most of the isolates, and a much larger number of species present with low frequencies. Five species (Nodulisporium sp., Acremonium strictum and three Phoma-like coelomycetes) represented more than 50% of the whole isolates. Coelomycetous anamorphs of ascomycetes bearing small, hyaline ameroconidia, were the most abundant group of fungi, whereas teleomorphs were rarely seen.